2006
DOI: 10.1080/10715760500540442
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant profile of dihydroxy- and trihydroxyphenolic acids-A structure–activity relationship study

Abstract: Eight structurally similar dihydroxy and trihydroxyphenolic acids (protocatechuic acid, 3,4-dihydroxyphenylacetic acid, hydrocaffeic acid, caffeic acid, gallic acid, 3,4,5-trihydroxyphenylacetic acid, 3-(3,4,5-trihydroxyphenyl)propanoic acid and 3-(3,4,5-trihydroxyphenyl)propenoic acid) were examined for their total antioxidant capacity (TAC). Furthermore, their ability to scavenge peroxyl radicals, generated by AAPH in liposomes, was determined. The antioxidant/pro-oxidant activity of the compounds was screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
105
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(124 citation statements)
references
References 36 publications
15
105
1
3
Order By: Relevance
“…The trihydroxybenzoic acid derivatives, gallic acid and propyl gallate showed very good scavenging activity. For phenolic acids, it was demonstrated that compounds presenting a pyrogallol unit (three hydroxyl groups on the phenol ring) exhibited higher antioxidant properties than those presenting a catechol unit (two hydroxyl groups on the phenolic ring) (Siquet et al 2006). Ferulic acid is more effective than p-coumaric acid due to the presence of the OCH 3 group in position ortho to the hydroxyl group.…”
Section: Abts +• Scavenging Activitymentioning
confidence: 99%
“…The trihydroxybenzoic acid derivatives, gallic acid and propyl gallate showed very good scavenging activity. For phenolic acids, it was demonstrated that compounds presenting a pyrogallol unit (three hydroxyl groups on the phenol ring) exhibited higher antioxidant properties than those presenting a catechol unit (two hydroxyl groups on the phenolic ring) (Siquet et al 2006). Ferulic acid is more effective than p-coumaric acid due to the presence of the OCH 3 group in position ortho to the hydroxyl group.…”
Section: Abts +• Scavenging Activitymentioning
confidence: 99%
“…Polyphenols are bioactive compounds believed to be involved in the defence process against deleterious oxidative damage, at least in part, due to their antioxidant properties (Fresco, Borges, Diniz, & Marques, 2006). Phenolic acids have been widely investigated as potential models for the development of new primary antioxidants, which can prevent or delay in vitro and/or in vivo oxidation processes (Siquet, Paiva Martins, Lima, Reis, & Borges, 2006). These phenolic compounds are powerful antioxidants and act in a structure-dependent manner, since they can scavenge reactive oxygen species (ROS), and chelate transition metals which play vital roles in the initiation of deleterious free radical reactions (Fresco et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Phenylpropanoids play important role as antioxidants (Kurkin 2013), which is related to the hydroxyl moiety of aromatic ring (Park et al 2003). SAR study shows that number of -OH groups and the nature of alkyl spacer between aromatic ring and carboxylic group play important role in antioxidant behaviour of a compound (Siquet et al 2006). Sesquiterpenoid hydroquinones and sesquiterpenoid quinones are also reported as antioxidant agents with hydroquinones being stronger as compared to quinones (Belisario et al 1992).…”
Section: Discussionmentioning
confidence: 99%